2013
DOI: 10.4028/www.scientific.net/amr.845.66
|View full text |Cite
|
Sign up to set email alerts
|

Spray Characteristic of Diesel-Water Injector for Burner System

Abstract: Abstract. NOx and PM are the major product results from the combustion of diesel either in internal combustion engine or external burner system. Thus, the emulsification concept from diesel and water were studied with focusing in controlling of combustion process in order to minimize the harmful emission. The main purpose of this research is to investigate the effects of diesel-water emulsification on mixture formation, burning process and flame development in burner system. The studed parameters include equiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…In the internal combustion engine, the combustion process can be divided into three specific broad regions which are ignition and flame development, flame propagation and flame termination [9][10]. The first phase of combustion is development of flame, the consumption of A/F mixture is only 5%.…”
Section: Introductionmentioning
confidence: 99%
“…In the internal combustion engine, the combustion process can be divided into three specific broad regions which are ignition and flame development, flame propagation and flame termination [9][10]. The first phase of combustion is development of flame, the consumption of A/F mixture is only 5%.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods will use for research to develop the properties and performances about the biodiesel. In modern technology, the rapid compression machine is an instrument designed to simulate a single small engine of an internal combustion engine [2][3][4][5]. For purpose of elementary study on diesel combustion, it is therefore advantageous to employ a single shot burning device compare to the ordinary engine.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [3,5,6] reported that spray penetration length is considerably affected by pressure supplied to the spray; moreover, the thermo-physical properties of the liquid do not control the spray characteristics. Khalid et al [7] evaluated spray characteristics by using water-emulsified diesel fuel with various water percentages and indicated that increasing the quantity of water decreases the fuel viscosity, leading to high spray penetration. Khalid et al [8] found that jatropha oil exhibits higher levels of spray penetration than diesel fuel [8].…”
Section: Introductionmentioning
confidence: 99%